The Relationship of Self Control and FOMO with the Tendency of Social Media Addiction in Korean Pop Fans - Sulistyawati, Hesti; Rosyidi, Hamim (International Conference on Sustainable Health Promotion, 2023)
This study aims to determine the relationship between self-control and FOMO with social media addiction tendencies in Korean pop fans. This research is a quantitative research, with a correlational research type. The subject of this research is Korean pop fans. The sample in this study was 100 respondents using accidental sampling technique. Data collection used a questionnaire on the Social Media Addiction Scale (SMAS), self-control scale, and the Online Fear of Missing Out (ON-FOMO) scale. Data analysis used multiple linear regression analysis test. The results of this study indicate that there is a positive significant relationship between the self-control variable and social media addiction tendencies with a significance value of 0.037, and FOMO with social media addiction tendencies with a significance value of 0.000 <0.05. Then together the variables of self-control and FOMO have a relationship with the tendency of social media addiction with a significance value of 0.000 and an effect of 0.373 <0.05 or 37.3%, the remaining 62.7% is influenced by other variables outside this study, so the hypothesis is accepted. The conclusion in this study is that there is a relationship between self control and FOMO with the tendency of social media addiction among Korean pop fans.